A Study of Biblical Valence on the Role of Church Women in Managing the Waste Bank Program in Manado - Rivay Bobby Palempung; Hendry C. M. Runtuwene (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study explores the integration of biblical values and women’s empowerment in community-based environmental stewardship through the Waste Bank program at Getsemani Church in Manado, Indonesia. Rapid urbanization and inadequate waste management have intensified ecological and social challenges, including flooding and public health risks. While faith communities are increasingly recognized as potential agents of sustainability, the role of theological motivation and gender dynamics in environmental actions remains underexplored. This study aims to analyze how biblical principles inform ecological practices and how women’s participation contributes to the effectiveness and sustainability of local waste management initiatives. A mixed-method approach was employed, combining qualitative case studies, participatory action research, quantitative surveys, and theological literature analysis. Data were collected from 25 key informants and 100 survey respondents supported by field observations and document reviews. The findings indicate that values such as stewardship (Genesis 2:15) and creation care (Psalm 24:1) serve as strong moral motivators, with a positive correlation (Pearson’s r = 0.68) between biblical literacy and program participation. Women constituted 75% of active participants, driving operational success, economic returns (average IDR 4.5/month), and community engagement. Their involvement has led to a 35% reduction in landfill-bound waste and improved drainage conditions, thus mitigating localized flooding. Furthermore, the program enhanced women’s financial autonomy and social recognition within the church and the broader community. The study concludes that faith-based environmental initiatives, when rooted in theological convictions and inclusive of women’s leadership, can generate tangible ecological, economic, and social impacts. This model offers a replicable framework for urban churches seeking to respond to ecological crises through spiritually grounded, community led action.